Vítimas indiretas dos homicídios: testemunho de mulheres em São Paulo/SP - Acquaviva, Graziela (2015)
This is a study about the impact of homicides in the indirect victims of these crimes, especially the family and among these, women. Starting from previous research results and records, performed in FAPESP Program of Public Policy, between 1998 and 2003, when it investigated the needs and demands of families with fatal victims and identified that 81% of respondents were women. From such data, and especially the social and political significance that is, considering the dominant gender perspective, where the house and the family are female. Daily exposure to violent territories pervades these houses and families and therefore women. Methodologically, the data were produced by reorganization of the evidence base, secondary in nature, consisting of digitized files of semi - structured interviews, field diaries and reports on criminal cases of the victims. The sample gathers common documentation of 80 cases. The analyzes refer to the profile of tracing of respondents and link between these and the many victims in the homes and in relation to security and justice system. Secondly, analyzes in greater depth, are made with reference to the daily research, considering the wealth of this source, in terms of the impact of fatal violence on the family, but also researchers. The link between the three sources, diaries, interviews and processes is undertaken by emphasizing the importance of the contribution of these in studies on violence, in direct contact with the individuals involved and, in this, especially on the indirect victims, hidden in research on deaths violent. The presence of women was marked in the houses, families and institutional relations with the opening of judicial investigations and processes. They were before, during and after the murders, objective living conditions, natural and invisible and comfortably, appropriate to State omission